(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: The anterior cruciate ligament reconstruction (ACLR) should not be delay too long to get a good outcome but how long delay could be considered acceptable is not known. The objective of this study was to assess the outcome of surgery performed within and after a year of injury. We also predicted the operative outcome if the surgery is further delayed and several associated factors were also evaluated if they could influence the outcome. Methodology: Thirty-six patients were recruited in the early group where surgery is performed within a year of injury and thirty were in the delayed group where surgery was after a year of injury. Age, sex, body mass index, Tegner activity level and duration from the time of injury to surgery were evaluated. Surgical outcomes were measured at one year follow up after surgery were Lysholm score and limb symmetry index (LSI). Results: Mean time from injury to surgery for early and delayed groups were eight months and 18 months. Timing from injury to surgery affects the outcome parameters. Both groups showed good outcomes but the early group showed better LSI and Lysholm scores (p<0.5). LSI was better in predicting the outcome of surgery compared to Lysholm score (67% vs 43%). Conclusions: Early ACLR showed better outcome but the late ACLR still demonstrate acceptable result in the absent of high grade cartilage lesion. LSI is better at predicting the outcome of surgery. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 876-881